2009
DOI: 10.1111/j.1365-2826.2009.01904.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide W has Cell Phenotype‐Specific Effects on the Excitability of Different Subpopulations of Paraventricular Nucleus Neurones

Abstract: Administration of the neuropeptides NPW and NPB in rodents has been shown to influence the activity of a variety of autonomic and neuroendocrine systems. The paraventricular nucleus is a major autonomic and neuroendocrine integration site in the hypothalamus and neurons within this nucleus express the receptor for these ligands, neuropeptide B/W receptor 1 (NPBWR1). Therefore we used whole cell patch clamp recordings coupled with single cell RT-PCR to examine the effects of neuropeptide W-23 (NPW-23) on the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Neuropeptide W (NPW) is produced in, and influences the membrane potential of, neurons in the PVN, an area of the brain that communicates extensively with preautonomic centers in the brain stem and spinal cord (9,17,18,19) and is important for the regulation of ingestive behaviors (5,19). Our laboratory previously reported the ability of exogenously applied NPW to significantly increase both food and water intake during the light phase (1).…”
Section: Discussionmentioning
confidence: 98%
“…Neuropeptide W (NPW) is produced in, and influences the membrane potential of, neurons in the PVN, an area of the brain that communicates extensively with preautonomic centers in the brain stem and spinal cord (9,17,18,19) and is important for the regulation of ingestive behaviors (5,19). Our laboratory previously reported the ability of exogenously applied NPW to significantly increase both food and water intake during the light phase (1).…”
Section: Discussionmentioning
confidence: 98%
“…Murao, 2005). Another study demonstrated that NPW23 influences the PVN neurons that synthesize oxytocin, vasopressin, and thyrotropinreleasing hormone (Price et al, 2009). These findings suggest that NPW neurons in the PVN are involved in neuroendocrine and autonomic regulation (Sakurai, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Of particular interest, Zaratin and coworkers reported increased expression of NPBW 1 receptor subtypes in myelin-forming Schwann cells in animal models of acute inflammatory and traumainduced neuropathic pain, suggesting a central role for this peptide as an analgesic (16). Price et al showed that direct injection of NPW-23 into the hypothalamus influenced the excitability of specific groups of neurons in rats (17,18). In short, NPW has been shown to be a multifunctional endogenous ligand for NPBW 1 (19).…”
mentioning
confidence: 99%
“…It has been previously reported that activation of NPBW 1 modulates hyperexcitability of neurons in the CNS (25). Price and co-workers previously reported that application of NPW to neurons in the paraventricular nucleus (PVN) of the hypothalamus resulted in a large population of hyperpolarized neurons (57%) with smaller mixed populations of depolarized and unchanged neurons (18). We hypothesize that the observed anticonvulsant effects exerted by hNPW-23, and the modified NPW analogues, resulted from activation of the NPBW 1 receptor which may result in hyperpolarization of the cell membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation